Students’ Conceptual Change On Human Reproduction Concept Using Scientific Approach - Lathifatuzzahra Taufiq; S Sriyati; D Priyandonko (Universitas Sebelas Maret, 2017)
This study aim was to describe students’ conceptual change and investigate the patterns of students’ conceptual change in human reproduction system concept through application scientific approach. The research method was weak experimental with one group pretest-post-test design and the number subject of this study were 34 students, 11th -grade students of SMAN 1 Indramayu. The instrument was three tier test which given at pretest and post-test. Data analyzed used qualitative and quantitative analysis. Qualitative analysis obtained through analyzed student answer then classified into category suitable. Quantitative analysis obtained through calculation N-gain value and one sample t test. The results showed mostly students had a misconception and lack of knowledge on all of the human reproduction concept. After a lesson, a conceptual change occurred, a percentage of students who have scientific concept increased from 27,74% to 79,23% and the average value of N-gain included into category medium (0,69). According to one sample t test, showed that there was a significant difference between post-test and minimum completeness criteria (KKM) value, 75 (amp. Sign 2 tailed = 0,048). Therefore, a scientific approach supported to build the concept. Furthermore, the analysis also showed students’ conceptual change patterns: changed to be positive, changed to be negative, still positive, and still negative. Pattern 4 (lack knowledge to be understanding a concept or changed to be positive) is the most which got 31,69%.